Behavioral intention to use knowledge sharing tools: Positive and negative affect on Affective Technology Acceptance Model - Lee, Angela Siew Hoong *; Lim, Tong Ming * (2016)
technology acceptance by extending TAM with positive and negative affect as external construct. This research attempts to study on the Knowledge workers that work in the Multimedia Super Corridor (MSC)-status organizations to understand their behavioral intention to use the knowledge sharing tools (KS tools) in their day-to-day tasks based on several motivators. KS tools in this research includes collaborative and communicative functions such as email, blog and Facebook. This research proposes Affective Technology Acceptance (A.T.A) Model that hypothesizes Positive and Negative Affect (PA and NA) have impact on Perceived Usefulness (PU), Perceived Ease of Use (PEOU) and Behavioral Intention to accept (BI) KS tools among knowledge workers in MSC organizations. Positive Affect (PA) and Negative Affect (NA) are defined as the perception of employees on KS tools that induce positive or negative affective states when they interact and evaluate these tools when execute their tasks